Sistem Informasi Keuangan Pada Lembaga Amil Zakat, Infaq, Sedekah Nahdlatul Ulama Kecamatan Limpung Berbasis Web - Azani Fajri, Laksamana Rajendra Haidar; Miftahurrohman; Haris Ihsanil Huda (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
The Amil Zakat, Infaq, and Sedekah Institution (LAZIS) of Nahdlatul Ulama in Limpung District plays a crucial role in managing community funds transparently and accountably. However, the manual financial system currently in use often hampers efficiency and accuracy in record-keeping. To address this issue, a web-based financial information system has been developed to facilitate the management of financial processes, including recording income, expenses, and generating real-time financial reports. This system is designed with key features such as donor data management, transaction recording for zakat, infaq, and sedekah, and the generation of financial reports accessible to relevant parties at any time. By leveraging web-based technology, the system provides ease of access for administrators and enhances transparency to the public. The development process follows the waterfall method, starting from requirements analysis to implementation and testing, ensuring the system meets user needs effectively. The implementation results indicate that the system significantly improves the efficiency and accuracy of financial management at LAZIS Nahdlatul Ulama Limpung District. Additionally, the system helps build public trust by providing more transparent and easily accessible financial reporting. As a result, the management of zakat, infaq, and sedekah funds becomes more structured, effective, and accountable.